Research on Robot Dynamic Handling System Based on Machine Vision and Online Tracking Technology. (May 2020) - Liu, Zhicheng; Bian, Shaoshun; Zhang, Bin; Lu, Zongxue; Zhou, Pengzhong; Lai, Lin
Abstract: In this paper, a set of dynamic handling control system based on Fanuc robot is designed and studied, in which the conveyor line positioning mechanism, industrial robot and stability mechanism are connected together by Siemens 1500 PLC as the main control unit. The machine vision and Fanuc robot tracking function are used to make dynamic visual photographs of the robot, which compensates for the deviation of the hanging rod and increases the success rate of the moving product. The monotonous and repeated manual labor can be solved, and the production efficiency and production quality of the enterprise can be improved by replacing the artificial handling with the robot handling.